Prolapso genital. Etiopatogenia, diagnóstico y tratamiento - Marambio G., Andrés; Sandoval S., César; Valdevenito S., Raúl; Naser N., Michel; Manríquez G., Valentín; Guzmán R., Rodrigo; Lecannelier A., Jorge; Abedrapo M., Mario; Jans B., Jaime; Aguilera M., Amalia (Revista Hospital Clínico Universidad de Chile, 2011)
Vaginal prolapse is a very common disorder in the general female population. Because it is so common and often asymptomatically, there is no exact definition of this condition. Additionally its exact prevalence is not known. There are multiple risk factors that cause vaginal prolapse, for example age and vaginal deliveries are the most common, nevertheless it is considered a multifactorial process. From the surgical point of view the most accepted theory for its production is site-specific tears that would generate the prolapse as they occur. Its diagnosis is clinical and is currently classified into four stages according to the degree of descent that exists with respect to the hymen. There are many different types of treatment, and the most used are pessaries, physiotherapy and surgery. The following is a review that covers various relevant aspects of the vaginal prolapse, his confrontation and treatment.